Azerbaijan Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix estimates the size of quasi-fiscal subsidies implicit in domestic energy policies in Azerbaijan. The paper highlights that from a consolidated public sector perspective, quasi-fiscal subsidies are no cheaper than fiscal or on-budget subsidies. Eventually, the budget bears the cost of the quasi-fiscal activity via reduced tax or dividend payments. The only difference between the quasi-fiscal subsidy and the on-budget subsidy is transparency. The paper also outlines a method for estimating energy-related quasi-fiscal subsidies.